Impact of implant–abutment connection, positioning of the machined collar/microgap, and platform switching on crestal bone level changes. Camlog Foundation Consensus Report. Issue 11 (21st October 2013) - Schwarz, Frank; Alcoforado, Gil; Nelson, Katja; Schaer, Alex; Taylor, Thomas; Beuer, Florian; Strietzel, Frank Peter
Abstract: Objectives: The aim of this consensus meeting was to assess the impact of implant–abutment connection, positioning of the machined collar/microgap, and platform switching on crestal bone level changes. Materials and methods: Two comprehensive systematic reviews were prepared in advance of the meeting. Consensus statements, practical recommendations, and implications for future research were based on within group as well as plenary scrutinization and discussions of these systematic reviews. Results: Placing the smooth part of the implant below the alveolar crest may lead to bone loss. Despite a more pronounced bone remodeling, the subcrestal positioning of the microgap may help to retain the bony coverage of the rough surface. Crestal bone remodeling has been observed for either internal and external, or conical and butt–joint connections. There was a trend favoring the platform switching concept to prevent or minimize peri‐implant marginal bone loss. Conclusions: Future research should consider an uniform and comparable study design, either excluding or exactly documenting possible confounding factors.